Cobalt and nickel uptake by silica-based extractants. Issue 10 (3rd July 2018) - Pepper, Sarah E.; Whittle, Karl R.; Harwood, Laurence M.; Cowell, Joseph; Lee, Taek Seung; Ogden, Mark D.
ABSTRACT: The pKa s of ethyl/butyl phosphonate silica (EBP-Si) have been determined, and the removal of cobalt and nickel from solution was investigated as a function of various parameters and compared with those of Purolite S950. pH uptake experiments suggested a combination of ion exchange and acid dissociation of the surface occurring. Isotherm data, fitted using the Langmuir and Dubinin–Radushkevich (D-R) models, indicated that stronger complexes formed with S950 than with EBP-Si. Kinetic data, fitted using a pseudo-second-order model, suggested that the rate-determining process is the reaction of metal ions with the chelating functionality of the resin. Uptake by EBP-Si is two to three times faster than that on S950.